The management of human talent and its relationship with the organizational identification of Intelidata workers, San Isidro-2019 - Roman Vergara, Freysa Medalith (2022)
This article had the general objective of determining the relationship that exists between the management of human talent and organizational identification. Case: Intelidata, San Isidro - 2019.  The research is correlational, the research design is non-experimental. The sample consisted of 16 workers from the Intelidata organization Perú, who responded to a questionnaire of 41 Likert-type questions. The results were analyzed using the statistical program IBM SPSS V26.The general hypothesis was accepted, with a correlation of 0.715, the value obtained is a considerable positive correlation, thus determining that there is a significant relationship between human talent management and the organizational identification. It is concluded that with an optimal management of human talent it will be possible to have identified workers, with a high level of belonging to the organization, the research reflects the great importance of people since they are the heart of any organization, a fundamental piece in organizational development.